Potential use of green coconut shell liquid in young dwarf coconut plants - Aguiar Freitas de Andrade, Hosana; guirado artur, adriana; Alberto Kenji Taniguchi, Carlos; de Barros Trannin, Isabel Cristina; Natale, William (Revista Ciência Agronômica, 2023)
The pressing of green coconut shell, aiming at the production of powder or fiber, used as raw material by the industry, generates large amounts of the green coconut shell liquid (GCSL), whose incorrect disposal results in environmental impacts. This study evaluated the potential use of GCSL as a source of potassium for young dwarf coconut plants. The experiment was carried out in pots, in a completely randomized design, applying seven treatments, comprising five doses of GCSL, which corresponded to 0% (G0), 50% (G50), 100% (G100), 150% (G150) and 200% (G200) of the need for K2O of the plants, a treatment with mineral fertilizer, corresponding to 100% of K2O supplied as KCl (K100), and another containing 50% of K2O as KCl and 50% as GCSL (G50 + K50), with five replicates. One hundred and twenty days after transplanting the seedlings, soil chemical attributes as well as growth and nutritional status of dwarf coconut plants were evaluated. Increase in GCSL doses altered soil fertility and reduced the percentage of live leaves of dwarf coconut. The G50 + K50 treatment did not differ from K100 for all variables of growth, except for % of live leaves, indicating the possibility of replacing 50% of the K2O dose recommended for the first year of dwarf coconut cultivation with GCSL.